2020
DOI: 10.4102/sajcd.v67i2.670
|View full text |Cite
|
Sign up to set email alerts
|

South African hearing conservation programmes in the context of tele-audiology: A scoping review

Abstract: Background: The limited involvement of audiologists in occupational noise-induced hearing loss (ONIHL) management through hearing conservation programmes (HCPs) is a global issue. In low- and middle-income (LAMI) countries such as South Africa, this is also exacerbated by demand versus capacity challenges. Tele-audiology is an option requiring serious deliberation by the audiology community within HCPs in LAMI contexts.Objectives: This scoping review explores if tele-audiology has a potential value in HCPs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…This is particularly important as definitive evidence is required to ensure that appropriate treatment is provided that takes into cognisance the therapeutic dilemmas surrounding the use of steroids in this population, as raised by Karimi-Galougahi et al ( 2020 ), the need for patient isolation and the possibilities of monitoring for late onset hearing loss in children born to mothers who were COVID-19 positive during pregnancy. The South African healthcare system and the audiology community would need to carefully plan around how to effectively manage these cases within the already resource-constrained context (Pillay et al, 2020 ), possibly within already existing programmes, adopting a programmatic approach to care (Khoza-Shangase, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important as definitive evidence is required to ensure that appropriate treatment is provided that takes into cognisance the therapeutic dilemmas surrounding the use of steroids in this population, as raised by Karimi-Galougahi et al ( 2020 ), the need for patient isolation and the possibilities of monitoring for late onset hearing loss in children born to mothers who were COVID-19 positive during pregnancy. The South African healthcare system and the audiology community would need to carefully plan around how to effectively manage these cases within the already resource-constrained context (Pillay et al, 2020 ), possibly within already existing programmes, adopting a programmatic approach to care (Khoza-Shangase, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…This concern is driven by the numbers of infections that have and continue to be high in the African context – with minimal success from vaccination drives because of vaccine hesitancy (Cooper, Van Rooyen, & Wiysonge, 2021 ; Hughes, Mbamalu, Okonji, & Puoane, 2021 ). With the numbers of infection and the documented capacity versus demand challenges insofar as provision of ear and hearing care services is concerned in South Africa (Pillay, Tiwari, Kathard, & Chikte, 2020 ), it becomes crucial that clear definition of morbidity, including cochleovestibular symptoms, in order to facilitate proper planning at all levels of preventive audiology from primordial to tertiary (Khoza-Shangase, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Teleaudiology emerged as a promising vehicle to deliver hearing health care to a larger population, mitigating the capacity versus demand challenges as far as extreme shortage of hearing health care practitioners is concerned. Khoza-Shangase and Moroe 23 strongly encourage the use of teleaudiology within the South African mining context to mitigate the challenges relating to access. Teleaudiological services imply that a hearing health care practitioner can remotely provide audiological care to patients.…”
Section: Teleaudiologymentioning
confidence: 99%
“…Telepractice and teletraining are options requiring serious deliberation within SLH professions in low-and-middle-income countries (LMICs), such as South Africa, not only to address the demand versus capacity challenge; but also, as a response to the direct contact restrictions brought by COVID-19. Benson (2020), for example, has reported that audiological assessment during COVID-19 should include video otoscopy, tympanometry and pure tone audiometry; which can all be conducted through real-time synchronous and asynchronous tele-audiology (Coco, 2020;Khoza-Shangase & Moroe, 2020). Ohannessian et al (2020) highlight that COVID-19 has also demonstrated the use of global health teleconsultations and tele-expertise as part of telepractice.…”
mentioning
confidence: 99%
“…Published evidence within the South African context is increasingly agitating for change and re-imagination of how training as well as service provision is provided ( Khoza-Shangase & Mophosho, 2018 , in press; Koens et al, 2020 ; Pillay & Kathard, 2018 ). Within SLH, Abrahams et al (2019) gleaned that increasingly literature focusing on clinical service provision is reflecting: (1) the need for transformation of the professions, depicted by the recognition of the importance of acknowledgement of the impact that linguistic and cultural diversity has on outcomes, coupled with development of culturally and linguistically appropriate assessment and intervention tools ( Barratt et al, 2012 ; HPCSA, 2019 ; Khoza-Shangase & Mophosho, 2018 ; Mdlalo et al, 2019 ); (2) the need for SLH practitioners to consider their own positionality in relation to the racial, linguistic and cultural diverse populations served ( HPCSA, 2019 ; Khoza-Shangase & Mophosho, 2018 ); and (3) the requisite to think creatively when considering the needs of the South African context ( Khoza-Shangase & Moroe, 2020 ; Maluleke et al, 2021 ; Moonsamy et al, 2017 ; Naude & Bornman, 2021 ).…”
mentioning
confidence: 99%